The Classical Parthenon Recovering the Strangeness of the Ancient World - st. clair, william (Open Book Publishers, 2022)
Complementing Who Saved the Parthenon? this companion volume sets aside more recent narratives surrounding the Athenian Acropolis, supposedly 'the very symbol of democracy itself', instead asking if we can truly access an ancient past imputed with modern meaning. And, if so, how? In this book William St Clair presents a reconstructed understanding of the Parthenon from within the classical Athenian worldview. He explores its role and meaning by weaving together a range of textual and visual sources into two innovative oratorical experiments - a speech in the style of Thucydides and a first-century CE rhetorical exercise - which are used to develop a narrative analysis of the temple structure, revealing a strange story of indigeneity, origins, and empire. The Classical Parthenon offers new answers to old questions, such as the riddle of the Parthenon frieze, and provides a framing device for the wider relationship between visual artefacts, built heritage, and layers of accumulated cultural rhetoric. This groundbreaking and pertinent work will appeal across the disciplines to readers interested in the classics, art history, and the nature of history, while also speaking to a general audience that is interrogating the role of monuments in contemporary society.